IMPLEMENTING AN AUTOMATED SYSTEM TO SIMPLIFY THE DATA MANAGEMENT PROCESS AT PARTS STORAGE AREA OF PT. Z - Azwir, Hery Hamdi; Maulidin, M. Yafi (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2017)
This research concerns about the design and implementation of a new information system which will simplify the processes of the current system and its impact on the warehouse staffs. In order to automate the processes, a programmed information system is designed using Microsoft excel VBA, a basic programming function inside Microsoft excel. First, the current system is analyzed. Next, the user requirements and proposed system requirements are analyzed to make the system design. Then, the program is developed and tested by using VBA (Visual Basic for Applications). Then, the new system is implemented and the implementation results are analyzed. The results found that the new system successfully fulfilled the objectives of this research and the user requirements, although there are still some improvements which need to be done. During two months’ period of implementation, there are some problems encountered which required the programmer to improve the system. Like every system, there are some advantages and disadvantages found in this new system.AbstrakPenelitian ini fokus kepada desain dan implementasi sistem informasi baru yang akan mengotomatisasi proses dari sistem saat ini dan dampaknya terhadap staf gudang. Dalam rangka untuk mengotomatisasi proses, sistem informasi yang terprogram dirancang menggunakan Microsoft excel VBA,sebuah fungsi dasar pemrograman dalam Microsoft excel. Pertama, sistem yang sekarang dianalisis. Selanjutnya, kebutuhan pengguna dan kebutuhan sistem yang diusulkan dianalisis untuk membuat desain sistem. Kemudian, program ini dikembangkan dan diuji dengan menggunakan VBA (Visual Basic for Applications). Kemudian, sistem baru diimplementasikan dan hasil dari implementasi dianalisis. Hasil penelitian menemukan bahwa sistem baru berhasil memenuhi tujuan penelitian ini dan kebutuhan pengguna, meskipun masih ada beberapa perbaikan yang perlu dilakukan. Selama periode dua bulan implementasi, ada beberapa masalah yang dihadapi yang membutuhkan programmer untuk mengembangkan sistemnya. Seperti setiap sistem, ada beberapa kelebihan dan kekurangan yang ditemukan dalam sistem baru ini.